ANALISIS EFEKTIVITAS PENYALURAN DANA ZAKAT PADA BAZNAS KABUPATEN ASAHAN TAHUN 2019-2022 - Supardi; Asyaadatun Nazila Selayan; Fadilla Yaumil Hasanah; Sugianto (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2023)
One of the performance indicators used in zakat institutions is assessing the effectiveness of the distribution of zakat funds so that zakat examiners can evaluate whether the zakat that has been distributed has been optimal or not. This study aims to determine the level of effectiveness of the distribution of zakat funds at BAZNAS Asahan District. This qualitative research was conducted by measuring the effectiveness of zakat distribution using the ACR (Allocation to Collection Ratio) ratio in the Zakat Core Principle model. The results showed that the level of effectiveness in channeling zakat funds at BAZNAS in Asahan Regency during the 2019–2022 period was 243%, including it in the highly effective category, namely having a very effective capacity in distributing zakat fundsKeywords: effectiveness, distribution of zakat funds, ACR, BAZNAS